Implementation of learning model talking stick with Crossword Puzzle model to increase IPS integrated learning outcomes grade VII SMP Negeri 11 Malang - Wiajayanti, Ratna Diyah; Istiqomah, Ni’matul (Unversitas Negeri Malang, 2017)
Based on observations and interviews with a social teacher at SMPN 11 Malang, obtained information that the learning process of a social subject is still using lecture method and to be one-way in the classroom. This causes less active students in learning so that activity in students to learn is still lacking. This will have an impact on student's mastery learning which is the minimum standard of mastery learning which has been established by SMP Negeri 11 Malang is 75%. To overcome these problems required learning model that can improve student learning activity. The model applied in this study is a learning model Talking Stick with Crossword. This research aims to determine the completeness of VII students in G class SMP Negeri 11 Malang through the Application of Learning Model Talking Stick with Crossword models. This research is a classroom action research (PTK), which consists of two cycles. The research data obtained from test results at the end of each cycle. The results show that in the first cycle, the completeness of students learning is 89% and increased in the second cycle become 100%. Keywords: Talking Stick Model, Crossword Puzzle Model DOI: 10.17977/um013v1i22017p058